Virtual Roaming of Cultural Heritage Based on Image Processing - Chen, Junzhe; She, Xing; Fan, Yuanxin; Shao, Wenwen (Computer animation and virtual worlds, 2024)
ABSTRACT With the digital protection and development of cultural heritage as a focus, an analysis of the trends in cultural heritage digitization reveals the importance of digital technology in this field, as demonstrated by the application of virtual reality (VR) to the protection and development of the Lingjiatan site. The implementation of the Lingjiatan roaming system involves sequential steps, including image acquisition, image splicing, and roaming system production. A user test was conducted to evaluate the usability and user experience of the system. The results show that the system operates normally, with smooth interactive functions that allow users to tour the Lingjiatan site virtually. Users can learn about Lingjiatan's culture from this virtual environment. This study further explores the system's potential for site preservation and development, and its role in the integration of cultural heritage and tourism.